Search for single b∗-quark production with the ATLAS detector at √s = 7 TeV - Aad, G. (2013)
The results of a search for an excited bottom-quark b* in pp collisions at s√=7 TeV, using 4.7/fb of data collected by the ATLAS detector at the LHC are presented. In the model studied, a single b*-quark is produced through a chromomagnetic interaction and subsequently decays to a W boson and a top-quark. The search is performed in the dilepton and lepton+jets final states, which are combined to set limits on b*-quark couplings for a range of b*-quark masses. For a benchmark with unit size chromomagnetic and Standard Model-like electroweak b* couplings, b*-quarks with masses less than 870 GeV are excluded at the 95% credibility level. The results of a search for an excited bottom-quark b^* in pp collisions at s=7 TeV, using 4.7 fb^-^1 of data collected by the ATLAS detector at the LHC are presented. In the model studied, a single b^*-quark is produced through a chromomagnetic interaction and subsequently decays to a W boson and a top quark. The search is performed in the dilepton and lepton+jets final states, which are combined to set limits on b^@?-quark couplings for a range of b^*-quark masses. For a benchmark with unit size chromomagnetic and Standard Model-like electroweak b^* couplings, b^* quarks with masses less than 870 GeV are excluded at the 95% credibility level.